Application of two fusion fixation systems in anterior cervical decompression and fusion surgery - ZHANG Chen, TIAN Jiwei, YU Xiao, LIU Xiaolei, WANG Haibin (Zhongguo linchuang yanjiu)
Objective：To compare the clinical efficacy of zero notch self stabilizing cervical fusion cage (ROI-C) versus titanium plate-based fusion devices in anterior cervical discectomy and fusion (ACDF) for the treatment of cervical spondylosis. Methods： A total of 112 patients with degenerative cervical spondylosis who underwent ACDF from December 2019 to October 2022 at the Fourth Affiliated Hospital of Nanjing Medical University were retrospectively analyzed. Among them, 63 cases were fixed with the ROI-C system (ROI-C group), 49 cases were fixed with titanium plate fusion devices (titanium plate group). The cervical dysfunction index (NDI), Japanese Orthopedic Association (JOA) score, Standardized Swallowing Assessment Scale (SSA) score, cervical spine curvature from C2 to C7 vertebral height of the operated segments, fusion device subsidence, and the incidence of other postoperative complications were collected from the patients in both groups at the preoperative and postoperative days 3, 1 month, and 12 months. Results： All patients underwent surgery successfully without any serious complications, and were followed up for 12-20 months, with an average of (14.39±1.81) months. There was no statistically significant difference in preoperative JOA, NDI and SSA scores, cervical curvature and height of intervertebral space at the operated segment between the two groups (P＞0.05). Cervical curvature, intervertebral space height, NDI and JOA scores were significantly improved in both groups at all postoperative time points compared with the preoperative period (P＜0.05), and SSA scores in the ROI-C group were significantly lower than those in the titanium plate group at the 3-day and 1-month postoperative follow-ups (P＜0.05). At the last follow-up, the incidence of fusion device subsidence was higher in the ROI-C group than that in the titanium plate group (23.8% vs 8.2%，χ2=4.790， P＜0.05). Conclusion： The use of two different fusion cage structures in ACDF can improve cervical function and quality of life. The ROI-C cervical cage can reduce the incidence of swallowing dysfunction, but the rate of fusion subsidence is increased.